Mapping Cognitive Engagement in Adult Literacy Classrooms - Thomas Valentine; Judy Milton; Anastasiya A. Lipnevich; Harold Beder (Adult Education Research Conference, 2006)
Using exploratory factor analysis to examine self-reported survey data from adult learners, this study identified three factors of cognitive engagement in the adult literacy classroom: program involvement, focus, and independent effort. A model that demonstrates the impact of independent effort on gains in reading test scores was developed using multivariate analysis.
Keywords: Adult literacy; cognitive engagement; quantitative research